Potensi Mineral Cassiterite dan Ilmenite pada Daerah Bekas Penambangan Timah Bangka - Dwi Putra Herman (PROMINE, 2015)
Mining and processing minerals can not to reach obtaining (recovery) one hundred percents. Mineralsthat thrown with tailing, are minerals pricy that can to be exploited back as value add for companyside. Before be done reklamasi and mine closing, necessary be knowing mineral 's potency that stillexist to mining ex area, to run the principle conservation of mineral resources. Research in mineralcassiterite and ilmenite that got to sediment tailing result tin washery, be done with way drilling withdistance 100 x 50 m in sediment localization mine tailing TN 3.10 Air Lempuyang PT Timah (persero)Tbk with coordinate UTM (633672 E; 9748033 N). Wide of area the mentioned research be counted itswide with to use it mapinfo program and the coordinate's withdrawal to use it Global PositioningSystem (GPS). Wide of area tailing's sediment to be guessed ± 9,74 ha. Drilling process to get itsample/ conto be done with to use it hand auger. S ampel mentioned be analyzed in physicslaboratory and chemistry that is grain counting minerals for 124 sample to know type and degree ofminerals, 1 komposit's sample be analyzed by classic method it’s volumetri and spectofotometri toknow total Fe total and degree of TiO2. Laboratory analysical Result, identificated mineral cassiterite,ilmenite, pyrite, iron oksida, limonite, muscovite, tourmalin, sand clay and quatz. With to use it themethod of area of influence calculation, be got resource number mineral cassiterite and ilmenite thatgot to sediment tailing mentioned.